Generalized van der Waals theory for phase behavior of two-dimensional nematic liquid crystals: II. Phase coexistence and adsorption - Soulé, Ezequiel Rodolfo (2020)
Adsorption of asymmetric particles or molecules into monolayers is important for many biological and technologically relevant physical systems. In-plane ordering can drastically affect adsorption and phase behavior. In this work, a generalized van der Waals theory previously developed [M. V. Zonta and E. R. Soulé, Phys. Rev. E 100, 062703 (2019)10.1103/PhysRevE.100.062703] is used to calculated phase behavior and adsorption isotherms in a system of hard-core rodlike particles with in-plane nematic order, as a function of the model parameters (aspect ratio L/B, isotropic and anisotropic interaction parameters χ and ν, and adsorption constant Kads). For small L/B, isotropic-nematic and/or (depending on χ) isotropic liquid-gas coexistence is observed; as L/B increases, coexistence between two different nematic phases appears at low temperature, and liquid-gas equilibrium ceases to be observed for large enough L/B; this is understood considering that as aspect ratio increases, the range of stability of the nematic phase becomes larger. Adsorption isotherms are found to significantly deviate from Langmuir behavior, and are strongly affected by ordering and interactions (surface density in the adsorbed layer increases as interaction parameters and ordering increase). Phase coexistence is observed as discontinuous transitions in adsorption isotherms, where adsorption-desorption hysteresis cycles are possible.